The Penerapan Kode Etik Jurnalistik Pasal 4 dan Pasal 5 Pada Berita Kekerasan Seksual Terhadap Anak Di Detik.Com - Khaliza, Dwi Nur (Universitas Gajah Putih, 2025)
This study aims to determine how Detik.com, as an online media outlet, implements the journalistic code of ethics in publishing news about sexual violence against children. This research uses a descriptive method with a qualitative approach. The results of the study indicate that news published by Detik.com in the May 2025 edition regarding sexual violence against children still contains violations of the journalistic code of ethics. The violations found include the indirect disclosure of the victim's identity, which makes it easier for others to trace the victim’s whereabouts, the explicit presentation of the news, and the use of sensational language that appears vulgar.